Students’ Perceptions in a Diverse Language Classroom: The Case of One Public University in Indonesia - Hesti Wahyuni Anggraini; Rita Hayati; Nova Lingga Pitaloka (Indonesian Research Journal in Education |IRJE|, 2020)
Diversity in language learning classrooms is important subject to study. Diversity affects students’ viewpoints and their success in language learning. Diversity does not exist without challenges; therefore, the emphasis here explored how diversity appeared and how the students accommodated the diversity to promote learning goals. This paper presented students ' perception of diversity in an English language classroom at one public university in Indonesia.  This exploratory study aimed to better understand diversity to meet students’ needs. By conducting a survey, the questionnaire and interview aimed to collect information about (a) demographic data (age, gender, and nationalities), but not limited to students’ level, culture and socioeconomic status, (b) students’ viewpoints about diversity and (c) how to accommodate the differences. The result showed that positive viewpoints referred to cultural awareness, knowledge acquisition and relationship while negative one referred to the difficulty to tolerate differences. Some recommendations are derived from the results.